Prozesstechnik zur Altholzaufbereitung. Issue 4 (15th February 2018) - Eisenlauer, Moritz; Graf, Hannah; Teipel, Ulrich
Abstract: In recent years the use of renewable raw materials has been gaining increasing importance. Therefore, new resource flows have to be developed and the process steps in the utilization chain need to be increased in their efficiency. Waste wood or recycled wood is still little used today. The upstream process of comminution is a key element in the usage of these materials. This work focuses on their comminution in a hammer and cutting mill. The influence of process parameters and the quality of the raw material on the comminution energy and the comminution products were investigated.